KHITAN PEREMPUAN DAN HUBUNGANNYA DENGAN HADIS NABAWI: STUDI LIVING HADIS DI SUKOWONO JEMBER - Safrina Auliya Fikriyah; M.Rizki Syahrul Ramadhan (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study examines the practice of female circumcision in Sukowono District, Jember Regency, through the perspective of living hadith. Female circumcision remains a socio-religious tradition passed down from generation to generation, although the hadiths used as its basis are disputed among scholars in terms of authenticity and legal status. This research aims to analyze the hadiths related to female circumcision, describe the forms of its practice in Sukowono, and explain the relationship between the practice and the community’s reception of the Prophet’s hadith. This study employs a qualitative field research method with a living hadith approach through observation, interviews, and documentation techniques. The findings reveal that the people of Sukowono continue practicing female circumcision because it is considered part of Islamic teachings and family tradition. The current practice tends to be symbolic and mild, involving slight scraping without excessive cutting. Most community members do not deeply understand the hadith texts or their sanad quality, yet the hadiths continue to live through tradition, the practices of traditional birth attendants, and collective social beliefs. This study concludes that the continuity of female circumcision in Sukowono is influenced more by socio-cultural reception of hadith than by direct textual understanding of the hadith itself.